Poesia, escrita quirográfica, leitura digital: a literatura de Pedro Gabriel - Bernardi, Heloisa (2017)
This study had the aim to research the Pedro Gabriel’s esthetics production published in written and digital medias, then researching how this production associates to the new statute of the literary production and esthetics reception and trough for two ways: the reading and the comprehension of texts of the writer published in media digital and written ; t he second one is a interview with the writer at that it will be discuss the ways and elements that point his art so the aspects together to reception of his texts. The research is a case study at the analysis of a interview with the writer and at the studies outside the texts as (comments, likes to the publications at the Facebook), it considering case the writer/ subject of the Pedro Gabriel’s work. For that was made a bibliographic research and after an outside research as the way case study. The hermeneutic research oriented for the comprehension of the poems published at the works: I call me Antônio (2013) at the social nets and the written way it is based on theorist tenet of the Pierre Lévy (1999,2011) and Lúcia Santaella (2004, 2010, 2013) about together intelligence, ciberculture and young readers associate also to sinKréticas notions of Massimo Canevacci (2005, 2013). The paper has with corpus the Pedro Gabriel’s poems, published at the Facebook and at the book I call me Antônio. The texts are build based on productions by hand, associating verbal texts and visual enunciation at the paper napkins used at night bars and after published as publication in social nets as with the same esthetics marks written in books that the same way have gotten a grow and mean number of “followers”.